Academic visit: National Library of Malaysia and National Archive of Malaysia - Kassim, Nor Hayati; Kamarudin, Nurfaizah; Halamy, Suhaida (UiTM Sarawak, 2024)
In conjunction with the Kuala Lumpur de laTour: Hope Utopia Project, 17 students and their lecturer, Nor Hayati Kassim from the School of Information Science, College ofComputing, Informatics and Media, UiTMSarawak paid a visit to the National Library of Malaysia (NLM) and the National Archive of Malaysia (NAM) in Kuala Lumpur. This program was held from November 27 to December 1, 2022. The aim of the visit was to help students deepen their understanding of the topics they have learned, thus providing them with practical reminders about what they can use in the examination hall.